ВПЛИВ БЮДЖЕТНОЇ ДЕЦЕНТРАЛІЗАЦІЇ НА ФУНКЦІОНУВАННЯ БЮДЖЕТУ РОЗВИТКУ (НА ПРИКЛАДІ БЮДЖЕТУ М. ТЕРНОПОЛЯ) (Світ фінансів, 2017)
Максимчук О. С. Вплив бюджетної децентралізації на функціонування бюджету розвитку (на прикладі бюджету м. Тернополя). Проаналізовано зміни в бюджетному законодавстві, які впливають на функціонування бюджету розвитку. Здійснено порівняльний аналіз доходів бюджету розвитку до і після внесення вищезазначених змін. Запропоновано шляхи забезпечення зростання ефективності функціонування бюджету розвитку. Обґрунтовано необхідність відокремлення бюджету розвитку від бюджету поточних витрат. Виявлено джерела зростання доходів бюджету розвитку. Максимчук А. С. Влияние бюджетной децентрализации на функционирование бюджета развития (на примере бюджета г. Тернополя). Проанализированы изменения в бюджетном законодательстве, влияющие на функционирование бюджета развития. Проведен сравнительный анализ доходов бюджета развития до и после внесения вышеуказанных изменений. Предложены пути обеспечения роста эффективности функционирования бюджета развития. Обоснована необходимость отделения бюджета развития от бюджета текущих расходов. Выявлены источники роста доходов бюджета развития. Maksymcyuk O. The impact of fiscal decentralization in Ukraine on the functioning of development budget (for example, the city budget of Ternopil). Introduction. Today no one doubts the need for decentralization, which should ensure the formation of self-sufficient communities. However, we must not forget that in addition to changing the ratio of state and local spending, decentralization must provide balance of expenditures for various purposes. At the present stage of the budgetary system of Ukraine, it does not ensure such balance.Purpose. Identification of the major problems in the functioning of the development budget based on the analysis of legislation and statistics and provide practical recommendations to improve the efficiency of its operation.Results. It is considered the definition of “fiscal decentralization”, highlighted its main aspects. It is characterized “Concept of reforming the local government and territorial organization of power in Ukraine.” It is analyzed changes in budget legislation that affect the operation of the development budget.Conclusions. For the effective functioning of the development budget should be implemented a range of measures. The priority of budget reform is separation of planning, funding and monitoring expenditure on recurrent expenditure with prospective expenditures. Also need to secure for him sufficient income to ensure implementation costs. In addition, Ukraine is necessary to form a reliable monitoring system.